Penampilan Agronomi 11 Varietas Unggul Baru Padi di Kabupaten Indramayu - HASTINI, TRI; DARMAWAN,; ISHAQ, ISKANDAR (Agrotrop : Journal on Agriculture Science, 2014)
The Performance of Agronomic Characters of Eleven New Superior Varieties of Rice atIndramayu Regency. The objective of the research was to investigate agronomic characters andcorrelation among those charactes of several new superior varieties of rice at Indramayu Regency. Thetrial was held in Sukahaji, Patrol, Indramayu during dry season 2013 and was arranged in RandomizedComplete Block Design with 11 rice varieties as treatment and repeated three times. The observationwas done for plant height, flowering age, harvesting time, number of productive tiller, number of filledgrainper panicle, number of unfilled-grain per panicle, 1000 grains weight and production. Data wasanalyzed using varian analysis and continued by DMRT at 5% level. Correlation was analyzed tounderstand relationship among agronomic characters. The result showed that agronomic charactersperfomance of each rice varieties being tested was determined by genetic and environment condition.The good adaptation capability varieties showed the best agronomic characters performance and highyield.Correlation among agronomic characters in rice was unstable and could change depend uponvarieties, treatment and environment condition. The best production was achieved by Inpari 10 andInpari 15.
Keywords: new varieties of rice; agronomic characters; correlation among characters